Community treatment for youth evidence-based interventions for severe emotional and behavioral disorders - Burns, Barbara J.; Hoagwood, Kimberly (New York : Oxford University Press, 2002)
These articles on children's mental health services in the US explore innovative community-based interventions for youth with serious emotional disorders. These include home-based services crisis care, therapeutic foster care and community mentors.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Youth -- Mental health services; Community mental health services; Adolescent psychiatry; Evidence-based medicine